Organisation Restructuring: The Influence of Interpersonal Conflict, Anomie, and Trust in Management on Counterproductive Work Behaviour - Rahim, Abdul Rahman Abdul; Noranee, Shereen; Othman, Abdul Kadir; Shabudin, Alwi; Anis, Azilah (International Journal of Management and Sustainability, 2018)
Employees’ reaction to organization restructuring varies as some react positively towards change but others refuse to accept it. Those who react negatively may engage in counterproductive work behavior. Since the existing studies are scarce in addressing this issue especially during organization restructuring, the present study is meant to investigate the influence of interpersonal conflict, anomie and trust in management on employees’ counterproductive work behavior. Data were collected from 215 non-managerial staff of a company offering maritime related services, which is undergoing restructuring exercise. Using a multiple regression analysis, it was found that trust in management and interpersonal conflicts negatively influence counterproductive work behavior while anomie or feeling helplessness or hopelessness positively influences counterproductive work behavior. The implications of the study are discussed in the paper.